Sensitivity of impact loading to landing strategy and physical profiles in drop landing - Gittoes, M.; Kerwin, D. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
This study aimed to gain an insight into the sensitivity of loading in drop landings to the selected strategy and physical profile of the performer. A wobbling mass model was used to simulate landings executed by two performers. Each performer`s physical profile was used to produce simulated motions employing the performer`s self-selected strategy and in landings replicated using another performer`s strategy. Impact loads were sensitive to changes in the strategy and physical profile of the performer. Changing the strategy altered the peak vertical ground reaction force (GFz) by up to 2.55 bodyweights (BW) and modifying the physical profile similarly changed the peak GFz by 2.52 BW. The execution of a strategy customized to a performer`s physical profile is potentially beneficial for reducing loading but may not fully alleviate the effects of a predisposing physical profile.